Riba Threat in al-Quran and Economic Crises - Mohd Shahid bin Mohd Noh (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
Every threat said by Allah in the Holy Al-Quran is definitive and could not be denied by human’s logical think and their limited effort. The threat that clearly stated in verse 279 Surah al-Baqarah to those riba practitioner, should bring its own interpretations and meanings that were justified by scholars and modern experts This paper relies on secondary sources from several books of tafsir, explainations of related contemporary Islamic scholars and also views from economic experts pertinent to riba practice implications that hit world economy so far, in effort to establish a linkage between them with the word of ‘harb’ as revealed in the verse. Hence, this paper finds that riba as practices widely in modern conventional banking system had brought negative impacts on economic sectors where it simultaneously effected on human activities. The term of inflation, deflation, recession and crisis always been heard and said since the early of 20th century until today